Developing a wearable device for upper extremity tremors - AKGÜN, GAZİ; GÜNAL, DİLEK; AKÜNER, MUSTAFA CANER; ŞEHİRLİ, ÜMİT SÜLEYMAN (My University, 2024)
Objective: This project aims to develop a wearable device to suppress both the essential and resting tremor and investigate its effectiveness. Materials and Methods: This study details the development and assessment of a wearable device for upper extremity tremors. The wearable device underwent a comprehensive design and a prototype was produced with a 3D-printer. To refine the functionality of the prototype, a motor that mimics tremor was attached to a 3D-printed prototype. Then, the printed prototype was applied to the hand model, and tested its effectiveness for tremor suppressing. The wearable device was further investigated on patients with essential tremor and Parkinson`s disease seeking treatment at Neurology Clinics. We recorded the tremor data and processed and visualized the recorded data by using the MatLab (version R2021a, MathWorks Inc., USA) software. Results: The wearable device effectively decreased the tremors both during the simulation phase and the patient testing phase. The data from the wearable device revealed a notable decrease in the amplitude of the tremor. This decrease signifies an achievement of tremor suppression. Conclusion: The prototype of the wearable device signifies a remarkable efficacy in tremor supression. It holds promise for being a potential solution to alleviate the tremor symptoms of essential tremor and Parkinson`s disease patients.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Essential Tremor; Parkinson`s Disease; Wearable device